Pengaruh Harga, Selera Konsumen, Dan Kualitas Produk Terhadap Kepuasan Konsumen Dilihat Dari Perspektif Manajemen Syariah (Studi Kasus: Sanjai Sil Aur Kuning Bukittinggi) - Maisaroh, Maisaroh; Nurani, Khadijah (Sains: Jurnal Manajemen dan Bisnis, 2023)
This study aims to analyze the effect of price, consumer tastes, and product quality on consumer satisfaction. This research is classified as quantitative. The approach used in this research is a descriptive quantitative approach. Sampling using purposive sampling method. The data used is primary data obtained from the owner Sanjai Sil, Aur Kuning Bukittinggi. While the data analysis technique used is Multiple Linear Regression, which includes Classical Assumptions Test, Instrument Test, Hypothesis Test, Multiple Linear Regression Analysis, Determinancy Test. analysis of this study uses SPSS 16, based on the results of the analysis of hypothesis testing T and F tests show that the independent variables (X1, X2, X3) partially affect the dependent variable (customer satisfaction / Y) while the value of X3 exceeds the established criteria, namely the value Sig, > 0.05 with a value of 0.87. Simultaneously X3 has no simultaneous effect on the dependent variable (Y) or H0 is rejected with a Sig value. >0.05.